Pengembangan Model Perencanaan Himpunan Data dan Aplikasi Instrumentasi Berbasis Pola Tujuh Belas Plus - Kusuma, Indra (NADWA, 2014)
This paper describes the development of a set of data and planning models based instrumentation applications seventeen plus patterns in BK teachers SMP / MTs in Bondowoso. The results of this study indicate that counselling activity plan-ning model using the approach pattern seventeen plus becomes very necessary. B.K. teachers in SMP/MTs of Bondowoso still do not have a wide range of data that should be held for the provision of counselling services. The teachers feel it is important to have variety of data sets and instrumentation applications for the smooth running of counselling services (score = 3.23). The evaluation of the implementation of set of data and applications instrument was still very low (score = 1.14). The planning model development activities and application in-strumentation data set found that B.K. teachers desperately need (score = 4.28). The assessment model development planning activities data set and instrumenta-tion applications that are promoted rated excellent (score = 4.47).Keywords: planning, data set, application instrumentation